2018
DOI: 10.1136/tobaccocontrol-2017-054178
|View full text |Cite
|
Sign up to set email alerts
|

Association between tobacco prices and smoking onset: evidence from the TCP India Survey

Abstract: BackgroundTobacco use is prevalent among youth and adults in India. However, direct evidence on how increasing taxes or prices affect tobacco use onset is scarce.ObjectiveTo analyse the associations between cigarette and bidi prices and smoking onset in India, and how these associations differ by socioeconomic status.MethodologyThe Wave 1 of the Tobacco Control Policy Evaluation India Survey by the International Tobacco Control Project contains information on the age at smoking onset for cigarettes and bidis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Five studies conducted in India 32 - 34 , 40 , 41 , two in Bangladesh 35 , 37 and one each in Nepal 42 , Thailand 43 , Sri Lanka 44 , Myanmar 39 , and Indonesia 38 , reported an inverse association between price and consumption of tobacco products ( Table 3 and Supplementary file Table S10). Of the 5 studies in India, two showed an inverse association between price and consumption exclusively for smoking tobacco (cigarettes and bidis) 40 , 41 , one exclusively for smokeless tobacco 34 , while the remaining two for both smoking and smokeless tobacco products 32 , 33 . The price elasticity of smokeless tobacco was between -0.09 and -0.87 (-0.0934, -0.5932, and -0.8733) while that for smoking tobacco was between -0.27 and -0.92; -0.92 33 and -0.27 32 for bidis, and -0.38 33 to -0.41 32 for cigarettes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies conducted in India 32 - 34 , 40 , 41 , two in Bangladesh 35 , 37 and one each in Nepal 42 , Thailand 43 , Sri Lanka 44 , Myanmar 39 , and Indonesia 38 , reported an inverse association between price and consumption of tobacco products ( Table 3 and Supplementary file Table S10). Of the 5 studies in India, two showed an inverse association between price and consumption exclusively for smoking tobacco (cigarettes and bidis) 40 , 41 , one exclusively for smokeless tobacco 34 , while the remaining two for both smoking and smokeless tobacco products 32 , 33 . The price elasticity of smokeless tobacco was between -0.09 and -0.87 (-0.0934, -0.5932, and -0.8733) while that for smoking tobacco was between -0.27 and -0.92; -0.92 33 and -0.27 32 for bidis, and -0.38 33 to -0.41 32 for cigarettes.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported the change in consumption of smokeless tobacco due to a change in smoked tobacco prices (cross price elasticity) 34 , 35 , 46 . Some studies also reported changes in cigarette prices leading to a significant shift to other tobacco product consumption 35 , 36 , 40 ; and vice-versa 33 , 49 . Three studies reported both the change in consumption and cross price elasticity of tobacco products in their respective findings 32 , 40 , 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These taxes are well below the tax rates on tobacco products recommended by the World Bank of 65-80% of the retail price 49 . In 2011 in India, the price of a single cigarette was US$0.026, whereas the price of a single bidi was US$0.0033 50 . Similarly, in 2016, retail price per pack of most brands of smokeless tobacco was US$0.10 36 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Shang et al 15 consider the impact of price changes on smoking initiation, for both cigarettes and bidis, in four states in India. Using a single wave of data, they create a pseudopanel dataset from respondents’ reported age at smoking onset and apply a discrete-time hazard (survival) model.…”
Section: Smoking Initiation and Quittingmentioning
confidence: 99%